Decrease in Social Zeitgebers Is Associated With Worsened Delayed Sleep-Wake Phase Disorder: Findings During the Pandemic in Japan - Otsuki, Rei; Matsui, Kentaro; Yoshiike, Takuya; Nagao, Kentaro; Utsumi, Tomohiro; Tsuru, Ayumi; Ayabe, Naoko; Hazumi, Megumi; Fukumizu, Michio; Kuriyama, Kenichi (Frontiers in Psychiatry, 2022)
Background Delay in sleep-wake rhythms was observed in the general population during the coronavirus disease 2019 (COVID-19) pandemic. Patients with delayed sleep-wake phase disorder (DSWPD) may have also experienced exacerbation of symptoms, but no studies have investigated this topic. In this study, we aimed to retrospectively examine the changes in symptoms of outpatients with DSWPD both before and during the pandemic and to identify the factors associated with the exacerbation of sleep-wake rhythms. Methods We included outpatients with DSWPD aged 16 years or older who visited the outpatient clinic due to sleep disorders between January and September 2020. Decreased social zeitgebers was defined as a reduction of 50% or more in the frequency of commuting to school or work during the COVID-19 pandemic. The severity of DSWPD was assessed using the clinical global impressions - severity of illness (CGI-S) at two points: before and during the pandemic. We defined the worsened, unchanged, and improved groups as those whose CGI-S scores worsened by at least one point, remained unchanged, and improved by at least one point, respectively. Multivariate logistic regression analysis was performed to determine the factors associated with worsened DSWPD symptoms. Results Sixty patients with DSWPD were eligible for this study. Even before the pandemic, patients who were unemployed or did not attend school tended to show more severe DSWPD symptoms. During the pandemic, 27 patients belonged to the worsened group; 28 patients, unchanged group; and 5 patients, improved group. Decreased social zeitgebers (odds ratio [OR] = 6.668, 95% confidence interval [CI]: 1.653–26.891, p < 0.05) and comorbid mood disorders (OR = 8.876, 95% CI: 1.714–45.974, p < 0.05) showed independent significant associations with the worsening of DSWPD symptoms. Conclusions During the pandemic, the symptoms of DSWPD tended to worsen. The obtained findings emphasize the importance of social zeitgebers, suggesting the need for external motivation in DSWPD treatment.